If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -12 = 90 Reorder the terms: -12 + 2x = 90 Solving -12 + 2x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2x = 90 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 90 + 12 2x = 90 + 12 Combine like terms: 90 + 12 = 102 2x = 102 Divide each side by '2'. x = 51 Simplifying x = 51
| 3m-5m-12=7m-88-500 | | 47/8-23/4=n | | (x-5)/(x-6) | | 11x+-24=-2 | | (6x^3-3x^2+5x+9)(7x+9)= | | 2(x-4)=x-0.25 | | 5n+4n=20 | | 6/5+1/7t=2 | | 3g+7-4=30 | | 13x-2=7x+22 | | (6a+4)(4a-6)= | | x^3=8graphed | | 13x-2=7x+2 | | 10x-(8+5x)=12x-2(4x-15) | | 11x+-24=2 | | -2x-2=3x+8 | | (5x^2+5x+7)(8x+6)= | | x+1/2=-7 | | (3x^2+4x+4)(2x-4)= | | C-15=6 | | -2(x-2)= | | 11x-4+7=124 | | 2xn=7 | | (5x^2+2x+8)(7x-6)= | | 27x+27=27 | | 0.10x+0.45(50)=28.5 | | -8-5x=42 | | 3x+7=5x+21 | | 3x+7=6x+21 | | 3/2(3x+1)=4(2-3x)+10 | | (4x^2)*(7/x) | | 33p+7=12-66p |